AI in advertising risks fuelling information crisis, UN warns (UN News, 2026)
With spending on advertising topping $1 trillion a year worldwide, the United Nations on Wednesday highlighted the untapped power of major brands to shape the future of Artificial Intelligence, warning that a failure to act could deepen a global information integrity crisis.
Worldwide